2018
DOI: 10.1080/13880209.2018.1448873
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of three new chromones from the leaves of Pimenta dioica with cytotoxic, oestrogenic and anti-oestrogenic effects

Abstract: Context:Pimenta dioica (L.) Merr. (Myrtaceae) is used in Costa Rican traditional medicine for women’s health. Our previous work showed that P. dioica extracts were oestrogenic.Objectives: This work identifies phytochemicals from P. dioica that are responsible for the plant’s oestrogen-like activities.Materials and methods:P. dioica leaves were collected in Costa Rica in 2005. Fractions resulting from chromatographic separation of a methanol extract were tested at 50 μg/mL in a competitive oestrogen receptor-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Anti-oxidant [87], anti-diabetic effects [89] and metabolic disorders via upregulation of TGR 5 [90]; oestrogenic effects, inhibitory effect on breast and gastric cancer cells [88].…”
Section: Female Inflorescences Of Humulus Lupulus (Hops)mentioning
confidence: 99%
“…Anti-oxidant [87], anti-diabetic effects [89] and metabolic disorders via upregulation of TGR 5 [90]; oestrogenic effects, inhibitory effect on breast and gastric cancer cells [88].…”
Section: Female Inflorescences Of Humulus Lupulus (Hops)mentioning
confidence: 99%
“…These biological properties of medicinal plants are exploited in the treatment of some estrogen-dependent ailments. Thus, Doyle et al [5] and Watcho et al [6] have respectively reported that Pimenta dioica and Bambusa vulgaris alleviate menopause-induced bone and metabolic damages. Erigeron floribundus (Asteraceae) is an herbaceous plant commonly found in Cameroon as a weed along roadsides.…”
Section: Introductionmentioning
confidence: 99%